18 Conscious sedation for transcatheter aortic valve implantation: is the anesthetist required?. (16th October 2019) - Prendiville, T; Tanner, R; Groake, S; Jacobsen, A; McGorrian, C; Moran, B; Casserly, I
Abstract : Introduction: In most US and European centers, trans-catheter aortic valve implantation (TAVI) is currently performed under conscious sedation with an anesthetist present. Due to lack of anesthetic resources, TAVI centers in Irish public hospitals typically perform TAVI under conscious sedation without an anesthetist present. We sought to assess the safety of this practice. Methods: Data from the prospectively collected Mater TAVI database were analyzed. Patients who underwent fully percutaneous trans-femoral TAVI, either without (Group A) or with (Group B) an anesthetist present, were identified and formed the study cohort. Baseline clinical, echocardiographic, and procedural variables were compiled for each group, in addition to procedure-related and in-hospital complication rates. Mortality and stroke rates at 1 month were assessed. Results: From the first 487 patients in the TAVI database, a total of 300 patients met the inclusion criteria. There were 85 patients in Group A (i.e., no anesthetist) and 215 patients in group B (i.e., anesthetist present). Baseline variables were similar except for a higher STS score in Group A (5.1 versus 4.4, p=0.050). Conversion to general anesthesia (GA) was more common in Group B, but was not statistically significant (1.2% versus 4.2%, p=0.292). Overall in-lab and in-hospital complication rates were similar in both groups (tables 1 and 2 ). Mortality and stroke rates at 1 month were also similar in both groups (3.5% versus 2.3%, p=0.568) (figure 1 ). Conclusion: In this non-randomized comparison, the strategy of performing TAVI with conscious sedation without an anesthetist present was associated with safety outcomes that were equivalent to those achieved when performing TAVI with conscious sedation supervised by an anesthetist, with a trend toward reduced rates of conversion to general anesthesia.